Pengetahuan Remaja Putri tentang Cara Melakukan Sadari - Sri Handayani; Sari Sudarmiati (Jurnal Keperawatan Diponegoro, 2012)
Breast cancer is one type of cancer which number of events is highest in Indonesia. Breast cancer cases in Sukoharjo increased from 402 cases in 2008 and reached to 685 cases in 2011. Breast cancer incidence is increased with increasing age. However, young age is also not a guarantee of safety of breast cancer because the risk of breast cancer begins in adolescence. Therefore, breast self-exam is very important in adolescents as a means of early detection of signs and symptoms of breast cancer. This study aims to assess knowledge and understanding of adolescence females in Bakalan Village about the way to do BSE (procedure, time, and the result of doing BSE). This study is a quantitative study using a descriptive survey method. Sampling method used a proportionate stratified random sampling which involved 202 respondents aged 12-22 years old. Data were collected using a questionnaire. Data were analyzed using univariate analysis to determine the frequency distribution and percentage of the characteristics and knowledge of respondents. The analysis found that 133 respondents (65,8%) have less knowledge about the way to do BSE, 92 respondents (45,5%) have less knowledge about procedure of BSE, 95 respondents (47%) have less knowledge about the time of BSE, and 94 respondents (46,5%) have less knowledge about the result of doing BSE. Parties Sukoharjo District Health and local health centers are expected to increase the knowledge of adolescence females about breast self-socialization program on BSE from an early age